Food Security and Sustainable Agriculture in the Face of Climate Change - Ahmed, Israr (Journal of Global Social Transformation, 2025)
The issue of climate change is a major threat to the world food security and the sustainability of agricultural systems. An increase in temperature, alteration of precipitation pattern, extreme weather, and change in pest and disease relationships negatively impact crop and animal productivity, food supply chain, and compound resource inadequacy. Sustainable agriculture such as climate-smart methods, efficient resource management, crop diversification, soil protection, and technological development is needed to provide greater resilience and secure food supply in the long-term perspective. This research article focuses on the multifaceted effects of climate change on food systems and how sustainable agriculture can be used as a mitigation and adaptation measure as well as policy and institutional actions required to reinforce food security. Using empirical research, case studies in the global and national level, and climate adaptation research, the article points out how the integrated strategies can cushion the food systems against climate shock, enable smallholder farmers and how it can still lead to wider development agenda. The results show that climate change is a major cause of agricultural disruptiveness and poses a threat to food supply, yet through sustainable solutions, with the aid of appropriate policies, investment, and stakeholder cooperation, risks could be reduced and promoting the development of resilient food systems achieved.
Keywords: climate change; food security; sustainable agriculture; climate-smart agriculture; resilience; adaptation; food systems; climate impacts